Organizations as Constitutional Systems - Vanberg, Viktor (Sociologija. Mintis ir veiksmas, 2000)
Translation: Vanberg, Viktor. 1992. "Organizations as Constitutional Systems". Constitutional Political Economy. 3: 223-253. Translated by Zenonas Norkus. (Second part of the article. The first one is published in the previous issue of "Sociologija. Mintis ir veiksmas", 1999-4).